Cover Feature: Rational Development of a Metal‐Free Bifunctional System for the C−H Activation of Methane: A Density Functional Theory Investigation (ChemPhysChem 19/2021). Issue 19 (7th October 2021) - Mahaut, Damien; Chardon, Aurélien; Mineur, Loïc; Berionni, Guillaume; Champagne, Benoît
Abstract : The Cover Feature shows the conceptually simple intramolecular frustrated Lewis pair 1‐aza‐9‐boratriptycene, which we demonstrate to be capable of activating methane using density functional theory. More information can be found in the Article by Benoît Champagne and co‐workers.